The urgency of the discovery learning model with a meaningful learning approach to enhance students critical thinking skills - Prasetyo, Dwi; Mulyani, Endang (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
In today’s world, critical thinking skills are essential for teaching economics. An initial observation at SMAN 2 Tulang Bawang Udik also indicated that the existing teaching methods did not support the development of higher-order thinking skills among students. This study was conducted to determine whether a combination of discovery learning and meaningful learning principles is necessary to foster critical thinking skills among students. A qualitative descriptive approach was employed, involving a sample of 60 grade 10 learners, 2 economics teachers, classroom observations, student surveys, and both structured and semi-structured interviews. Results showed that during lessons, 88% were passive, 62 per cent were below the minimum competency level, and 87% experienced difficulties with abstraction. Furthermore, 85% of students felt that the learning approach was overly theoretical, while most preferred a discovery-based approach. Teachers supported the use of innovative learning models. These results underscore the urgent need for an integrated economics curriculum that incorporates student-centred teaching through discovery and meaningful learning environments to enhance critical thinking skills.